2018
DOI: 10.2139/ssrn.3294371
|View full text |Cite
|
Sign up to set email alerts
|

Deviant or Wrong? The Effects of Norm Information on the Efficacy of Punishment

Abstract: A stream of research examining the effect of punishment on conformity indicates that punishment can backfire and lead to suboptimal social outcomes. We examine whether this effect is due to a lack of perceived legitimacy of rule enforcement, enabling agents to justify selfish behavior. We address the question of punishment legitimacy by shedding light upon the importance of social norms and their interplay with punishment. Often people are presented with incomplete norm information: either about what most othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Specifically, recent work -particularly in the field -has revealed that reminding people about descriptive and injunctive norms can lead to a positive behavioral response, especially when implemented with care and regard for the cultural and institutional circumstances (e.g., Hallsworth et al, 2017;Hernandez et al, 2017;Bott et al, 2019, and see also discussion in Bicchieri and Dimant, 2019). Importantly, the literature has also produced conflicting results in that not all interventions are equally successful, as some interventions have been observed to yield no effect or even a backfiring effect (e.g., Blumenthal et al, 2001;Fellner et al, 2013;Bicchieri et al, 2019c).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, recent work -particularly in the field -has revealed that reminding people about descriptive and injunctive norms can lead to a positive behavioral response, especially when implemented with care and regard for the cultural and institutional circumstances (e.g., Hallsworth et al, 2017;Hernandez et al, 2017;Bott et al, 2019, and see also discussion in Bicchieri and Dimant, 2019). Importantly, the literature has also produced conflicting results in that not all interventions are equally successful, as some interventions have been observed to yield no effect or even a backfiring effect (e.g., Blumenthal et al, 2001;Fellner et al, 2013;Bicchieri et al, 2019c).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…While we find that simple norm-nudges can be unsuccessful at shifting norms in environments in which a behavioral norm is already in place (cheating is normatively not acceptable, as our results from the Krupka and Weber (2013) et al, 2019b), which in turn may undermine the effectiveness of norm-nudges. The extent to which the effectiveness of norm-interventions is mediated by the common perception of an existing norm is subject to scientific debate (see, e.g., Bicchieri et al, 2019c) and requires further research. In addition, while our results can speak to the effectiveness of such interventions when the risk of detection for deviant behavior is absent by design (in our case implemented through the mind game as per Jiang, 2013), the results may or may not be comparable when risk of detection is present (as is often the case in the standard dice paradigm of Fischbacher and Föllmi-Heusi, 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There, personalized messages -and sometimes physical letters -are being sent with the intent to achieve behavior change in the forms of increasing tax compliance, charitable giving, primary school enrollment, and student learning, or in the form of decreasing energy consumption, student absenteeism from school, credit card debt, and even the spread of HIV infections, among other examples (Reinikka and Svensson, 2005;Dupas, 2011;Luttmer and Singhal, 2014;Boyer et al, 2016;Brandon et al, 2017;Rogers and Feller, 2018;Bursztyn et al, 2019). In existing literature, such information-only interventions indicate mixed results, with some studies demonstrating success (Hallsworth et al, 2017;Hernandez et al, 2017;Bott et al, 2019) while others either fail to detect a significant effect (Blumenthal et al, 2001;Fellner et al, 2013;Castro and Scartascini, 2015;Kettle et al, 2017;Cranor et al, 2018;Dunning et al, 2019) or indicate that interventions may backfire (John and Blume, 2018;Bicchieri et al, 2019c).…”
Section: Introductionmentioning
confidence: 99%